Are Components of the Medical Home Differentially Associated With Child Health Care Utilization, Health, and Health Promoting Behavior Outcomes?. (May 2013) - Long, Webb E.; Cabral, Howard J.; Garg, Arvin
Objective. To determine if specific components of the medical home are differentially associated with beneficial child outcomes. Methods. Logistic regression was used to model each component (family-centeredness, comprehensive care, and care coordination) with health care utilization, child health, and health promoting behaviors in 81 232 subjects from the 2003 National Survey of Children's Health. Results. Family-centeredness was associated with increased odds of children being read to (adjusted odds ratio [aOR] = 2.16). Comprehensive care was associated with decreased outpatient (aOR = 0.70) and emergency department (aOR = 0.79) sick visits and with increased child health per parental assessment (aOR = 1.50). Care coordination was associated with increased preventive care visits (aOR = 1.41) and increased outpatient (aOR = 1.21) and emergency department (aOR = 1.24) sick visits. Stratification by special health care needs demonstrated similar findings. Conclusions. Comprehensive care was associated with improved child health and health care utilization. Prospective studies are needed to further investigate the differential impact of components of the medical home on child health.